Peran Direktorat Jenderal Bea dan Cukai dalam Mencegah Penyelundupan Sabu Lintas Negara di Pos Lintas Batas Negara di Kecamatan Entikong, Kabupaten Sanggau, Provinsi Kalimantan Barat - Muhammad Syahrial; Hermini Susiatiningsih (Journal of International Relations Diponegoro, 2018)
This research aims to explain role of the Directorate General of Customs and Excise inpreventing cross-country methamphetamine smuggling from Malaysia to Indonesia from2012-2016 at the cross-border post in Entikong Sub-district, Sanggau District, WestKalimantan Province (PLBN Entikong). The method used in this study is qualitative withthe type of descriptive research. The results of this study explain that the role of theDirectorate General of Customs and Excise in preventing cross-country methamphetaminesmuggling from Malaysia to Indonesia from 2012-2016 at the cross-border post inEntikong Sub-district, Sanggau District, West Kalimantan Province (PLBN Entikong) is asa border protector by implementing various preventive actions based on Indonesia'snational interests in the field of security, economy and health.